Assessment of the Potential of Elementary School Students in Terms of Physical Fitness - Suroto, Suroto; Yustanti, Wiyli; Prakoso, Bayu Budi; Priadana, Benny Widya; Febriyanti, Irma (Mimbar Sekolah Dasar, 2024)
Primary education is an essential foundation for developing all the potential possessed by students, including physical fitness. The persistent inadequacy in children's physical fitness levels raises critical concerns regarding their overall health and well-being, necessitating urgent attention and intervention. This study aimed to assess the physical fitness of elementary school students, evaluate the effectiveness of the Indonesian Physical Fitness Test in measuring their physical fitness, and give policy recommendations. The quantitative descriptive method was used in this study due to its ability to provide numerical data analysis, facilitate systematic measurement, and allow comparative analysis and generalization. Incidental sampling was used to select 120 primary school learners in the Sidoarjo district. Two sets of fitness tests were administered based on child development phases: the Around the World Test for Phase B and a 600m running test for Phase C. Crosstabs analysis on SPSS revealed that male and female learners exhibited similar physical fitness levels, mainly within moderate and healthy categories. Differences were observed based on the phase or grade level (chi-squared=43.843, p=0.000), with Phase B learners generally having moderate to good fitness, while Phase C learners demonstrated lower and middle levels. Overall, there was a decline in fitness with higher grade levels, emphasizing the necessity to rejuvenate physical education for enhanced fitness. Instilling the importance of maintaining and enhancing physical fitness from a young age is crucial, and both teachers and students can actively contribute by enhancing their comprehension of physical literacy through training or by integrating it into the physical education curriculum.